2009
DOI: 10.1089/cap.2008.0103
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Metabolizing Enzyme Genotypes and Aggressive Behavior Treatment Response in Hospitalized Pediatric Psychiatric Patients

Abstract: Objective: The aim of this study was to examine the association between the CYP2D6 and CYP2C19 genotypepredicted combined phenotypes and short-term measures of psychotropic efficacy and toxicity. Methods: A rater-blinded, retrospective genotype association design examined a cohort of hospitalized pediatric psychiatric patients genotyped for CYP2D6 and CYP2C19 as part of clinical care. These combined genotypes were used to predict a combined phenotype. The primary efficacy outcome measure was the behavior inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Our study adds to a growing body of research demonstrating the feasibility of using retrospective EMR data for pharmacogenetic research in the inpatient psychiatric setting (Prows et al, 2009; Jukic et al, 2018). As EMR data extraction becomes increasingly automated, we offer a model for investigating relationships between pharmacogenetics and treatment outcomes using retrospective EMR data in the psychiatric setting.…”
Section: Discussionmentioning
confidence: 98%
“…Our study adds to a growing body of research demonstrating the feasibility of using retrospective EMR data for pharmacogenetic research in the inpatient psychiatric setting (Prows et al, 2009; Jukic et al, 2018). As EMR data extraction becomes increasingly automated, we offer a model for investigating relationships between pharmacogenetics and treatment outcomes using retrospective EMR data in the psychiatric setting.…”
Section: Discussionmentioning
confidence: 98%
“…7 A similar association of poor metabolizers having greater treatment response and higher incidence of side effects was demonstrated in a study of psychiatrically-hospitalized pediatric patients treated with psychotropic medications. 36 A study of autistic children treated with risperidone monotherapy revealed polymorphisms in the 5-HT 2A receptor as well as the 5-HT 2C receptor. A BDNF-related polymorphism produced treatment-related increases in prolactin while polymorphisms in the 5-HT 2C receptor as well as CYP2D6 phenotype predicted risperidone-related increases in BMI and/or waist circumference (Correia et al 2010).…”
Section: Pharmcogenomic Testing and Pharmacodynamicsmentioning
confidence: 99%
“…This hope was shown to be a potentially useful tool on inpatient pediatric psychiatric units in a retrospective analysis (Prows et al 2009). They examined the correlation between the CYP2D6 and CYP2C19 genotype-predicted combined phenotype and a behavioral intervention score to measure psychotropic efficacy as well as the drug's tolerability by reported adverse reactions.…”
Section: Discussionmentioning
confidence: 99%